2014
DOI: 10.3109/10837450.2014.882940
|View full text |Cite
|
Sign up to set email alerts
|

PLGA micro and nanoparticles in delivery of peptides and proteins; problems and approaches

Abstract: During the last decades, many of the poorly controlled diseases were treated using newly developed peptide and proteins. Although the majority of such therapeutic moieties have undesirable pharmacokinetic properties and there is still need for administration in relatively short intervals, new formulation strategies allow us to select appropriate carriers in the development of these compounds. Polyesters such as polylactide-co-glycolide were used to stabilize and control the release rate of peptide and proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 69 publications
6
80
0
Order By: Relevance
“…We explored alternatives for liposomes such as hydrophobic NPs that can be more easily stored and shipped. Poly( D , L -lactide-co-glycolide) (PLGA) is an FDA-approved biodegradable copolymer with excellent biocompatibility properties and long shelf-life21. We coated PLGA NPs with DMPC, stored them for 1 year at 4 °C to test the shelf-life and incubated them with Wnt3a protein, followed by dialysis to remove CHAPS.…”
Section: Resultsmentioning
confidence: 99%
“…We explored alternatives for liposomes such as hydrophobic NPs that can be more easily stored and shipped. Poly( D , L -lactide-co-glycolide) (PLGA) is an FDA-approved biodegradable copolymer with excellent biocompatibility properties and long shelf-life21. We coated PLGA NPs with DMPC, stored them for 1 year at 4 °C to test the shelf-life and incubated them with Wnt3a protein, followed by dialysis to remove CHAPS.…”
Section: Resultsmentioning
confidence: 99%
“…The incomplete release obtained in this study is frequently observed in such protein controlled release systems (Morille et al, 2013;Simón-Yarza et al, 2013;White et al, 2013). This phenomenon may be attributed to many destabilizing mechanisms occurring during the incubation period such as moistureinduced aggregation, adsorption onto the polymer surface, and acid-induced aggregation due to polymer degradation (Bilati et al, 2005;Mohammadi-Samani and Taghipour, 2014). Numerous approaches have been proposed to overcome this phenomenon like the use of basic salts or other additives in the formulation, replacement of classical polymers by more hydrophilic ones, and the use of pegylated proteins or ion-pairing proteins with polyelectrolytes (Giteau et al, 2008b;Taluja et al, 2007).…”
Section: In Vitro Release Studymentioning
confidence: 89%
“…An early challenge driving the passage of microcapsules into immunotherapy research was the inability to stabilize proteins in PLGA microspheres . Due to the exposure of encapsulated content to organic solvents, the stability and activity of biological cargo were often compromised.…”
Section: Microscale Materials For Immunotherapymentioning
confidence: 99%